Infant sleeping arrangements and cultural values among contemporary Japanese mothers - Shimizu, Mina; Park, Heejung; Greenfield, Patricia M. (Frontiers in Psychology, 2014)
We examined infant sleeping arrangements and parenting ethnotheories of Japanese mothers in 2008 and 2009. Based on Greenfield's theory of social change and human development, we predicted that social change in Japan over the last decades (higher economic and education level, urbanization, complex technology, more women in the work force) would lead to a decline in mother-infant cosleeping, compared with published findings concerning Japanese sleeping arrangements in the 1960s and 1980s. We also predicted that the practice of having babies sleep in their own beds and/or own rooms would be supported by ethnotheories stressing infant independence and other values adaptive in an urban, technologically sophisticated, relatively wealthy, and highly educated populace. Fifty-one Japanese mothers’ comments posted on Internet parenting forums were analyzed. Contrary to our hypothesis, cosleeping was as frequent among Japanese mothers in 2008-2009 as it had been in the 1960s and 1980s. However, analysis of the values of cosleeping mothers revealed frequent discrepancies between values and practices. In contrast, the minority of mothers whose babies slept alone in a separate room all expressed consonant ethnotheories. Our qualitative analysis indicates that it is not always easy for Japanese mothers to construct values for child rearing and gender roles that integrate traditional infant care practices with current sociodemographic conditions.